IR-visible upconversion and thermal effects in Pr3+/Yb3+-codoped Ga2O3 : La2S3 chalcogenide glasses - Santos, P. V. dos; Gouveia, E. A.; De Araujo, M. T.; Gouveia-Neto, A. S.; Ribeirot, S. J. L. [UNESP]; Benedicto, S. H. S. [UNESP] (Iop Publishing Ltd, 2000)
IR-visible upconversion fluorescence spectroscopy and thermal effects in pr(3+)/Yb3+-codoped Ga2O3:La2S3 chalcogenide glasses excited at 1.064 mum is reported. Intense visible upconversion emission in the wavelength region of 480-680 nm peaked around 500, 550, 620 and 660 nm is observed. Upconversion excitation of the Pr3+ excited-state visible emitting levels is achieved by st combination of phonon-assisted absorption, energy-transfer and phonon-assisted excited-state absorption processes. A threefold upconversion emission enhancement induced by thermal effects when the codoped sample was heated in the temperature range of 20-200 degreesC is demonstrated. The thermal-induced enhancement is attributed to a multiphonon-assisted anti-Stokes process which takes place in the excitation of the ytterbium and excited-state absorption of the praseodymium. The thermal effect is modelled by conventional rate equations considering temperature-dependent effective absorption cross-sections for the F-2(7/2)-F-2(5/2) ytterbium transition and (1)G(4)-P-3(0) praseadymium excited-state absorption, and it is shown to agree very well with experimental results. Frequency upconversion in singly Pr3+-doped samples pumped at 836 nm and 1.064 mum in a two-beam configuration is also examined.
Keywords: Fluorescence; Gallium compounds; Infrared spectroscopy; Lanthanum compounds; Mathematical models; Phonons; Positive ions; Praseodymium; Thermal effects; Ytterbium; Chalcogenide glasses; Conventional rate equations; Infrared visible upconversion fluorescence spectroscopy; Intense visible upconversion emission; Multiphonon assisted anti Stokes process; Thermal induced enhancement; Glass